Application of differential methods of global navigation satellite systems in mobile objects’ current coordinates determination - Харченко, В.П.; Кондратюк, В.М. (Proceedings of National Aviation University (archive), 2010)
Methods, features and particular ways of satellite navigation using the inverse differential method realization are investigated. The hardware-software facilities of inverse differential method implementation are proposed. The results of experiments are presented.